2016
DOI: 10.3171/2015.4.jns142129
|View full text |Cite
|
Sign up to set email alerts
|

Live-cell imaging to detect phosphatidylserine externalization in brain endothelial cells exposed to ionizing radiation: implications for the treatment of brain arteriovenous malformations

Abstract: Brain arteriovenous malformations (AVMs) are congenital abnormalities that consist of direct connections between arteries and veins, allowing highpressure arterial blood to flow into fragile cerebral veins, resulting in a high risk of hemorrhagic stroke. 16,37 The aim of AVM treatment is to prevent hemorrhage. 29 Treatment is effective only with complete AVM removal or obliteration. 14 Current treatments-namely surgery, endovascular occlusion, or stereotactic radiosurgery-are all associated with significant li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…In addition, radiation therapy has been reported to enhance PS exposure on tumor endothelium, serving as a potential radiation-stimulated target in future clinical applications [25,26]. Our recent studies also demonstrated significant externalization of endothelial PS upon radiation both in vitro, in brain microvascular endothelial cells, and in vivo, using a rat model of AVM [11,12]. This suggests PS could be used as a vascular target in irradiated AVMs.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…In addition, radiation therapy has been reported to enhance PS exposure on tumor endothelium, serving as a potential radiation-stimulated target in future clinical applications [25,26]. Our recent studies also demonstrated significant externalization of endothelial PS upon radiation both in vitro, in brain microvascular endothelial cells, and in vivo, using a rat model of AVM [11,12]. This suggests PS could be used as a vascular target in irradiated AVMs.…”
Section: Introductionmentioning
confidence: 62%
“…Hence, we aim to use radiosurgery to prime the AVM endothelium to induce potential targets. Our previous studies demonstrated that radiation can induce upregulation of surface biomarkers on the AVM endothelium thus discriminating it from normal vessels [10][11][12][13][14]. These proteins may serve as potential targets for ligand-directed pro-thrombotic conjugates, enhancing the thrombotic response when induced with radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Cells were used between passages 18-24 and passaged with 0.1% Trypsin/EDTA. Cells were seeded in 6-well plates for protein extraction, 8-well chamber slides (Thermoscientific) for immunocytochemistry or 75 cm 2 flasks for biotinlabelling at 30% confluence and irradiated with X-rays (20 Gy) generated by a 6 MV linear accelerator (LINAC, Elekta Synergy, Crawley, UK) at Macquarie University Hospital (Sydney, Australia) as previously described [67]. Control cells were treated identically but received no radiation.…”
Section: Methodsmentioning
confidence: 99%
“…Several in vitro and in vivo studies demonstrated endothelial cell apoptosis as an early event after irradiation. However, it was induced only by high doses of irradiation and was accompanied by strong inhibition of endothelial cell proliferation capacity (110, 111). The rate of apoptotic endothelial cells was estimated to be around 15% within 24 h after irradiation with high doses (112, 113).…”
Section: Inflammation-mediated Mechanisms In Radiation-induced Brain mentioning
confidence: 99%